The McDonaldisation of police–academic partnerships: organisational and cultural barriers encountered in moving from research on police to research with police - Goode, Jackie (Policing and society, 2018)
Partnerships between police and academics have proliferated in recent years, reflecting the increased recognition of the benefits to be had on both sides from collaborating on research, knowledge transfer and other activities. The literature on police–academic partnerships refer to inherent obstacles in bringing the ‘two worlds’ of research and practice together, and reflects an increased recognition on both sides of the benefits to be had from the co-production of research – reflecting a shift from conducting research on police, to conducting research with police. This takes place in the wider context of moves towards evidence-based policing, and the professionalisation of policing in the UK. In this paper we reflect on our experiences of building a police–academic partnership, focusing on: (1) the internal organisational and cultural drivers and barriers; (2) the opportunities offered via ‘in-house’ research by analysts and police officers and (3) evaluation. We highlight the increasing risk presented to both sides by the ‘McDonaldisation’ [Heslop, R., 2011. The British police service: professionalization or ‘McDonaldization’? International journal of police science & management, 13 (4), 312–321, Ritzer, G., 2004. The Mcdonaldization of society. London: Sage] of police–academic partnerships, and the need to thus play close attention to how the identification and prioritisation of research, its conduct, and aspects of evaluation, are managed and supported in practice, with open and transparent dialogue between police and academic partners. The paper draws on qualitative interviews conducted with police officers and police staff, and our observations and reflections while conducting a strategically driven university-police collaborative project with police forces in England.